1999
DOI: 10.1007/s11661-999-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the phase equilibria in the Sn-Bi-In alloy system

Abstract: This article presents an investigation of the phase equilibria in the Sn-Bi-In ternary alloy system, performed both by theoretical and experimental methods. Following the regular solution model and a standard thermochemical calculation, a theoretical evaluation of the phase equilibrium in the entire ternary system is conducted. The thermodynamic parameters required for the calculation are initially obtained by fitting the model to existing data available from prior studies. The theoretical results are then val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 15 publications
3
20
0
2
Order By: Relevance
“…While the phase-transition temperatures are generally in agreement, the new phase diagram represents a different nature of the quasi-binaries, the number and type of the invariant reactions, and the reaction paths [23]. It is found that the Sn-BiIn and Sn-BiIn 2 quasi-binary systems are not pseudobinaries, which eventually leads to a phase diagram with only one eutectic reaction.…”
Section: Hcp_a3mentioning
confidence: 83%
See 4 more Smart Citations
“…While the phase-transition temperatures are generally in agreement, the new phase diagram represents a different nature of the quasi-binaries, the number and type of the invariant reactions, and the reaction paths [23]. It is found that the Sn-BiIn and Sn-BiIn 2 quasi-binary systems are not pseudobinaries, which eventually leads to a phase diagram with only one eutectic reaction.…”
Section: Hcp_a3mentioning
confidence: 83%
“…The phase diagram of the Bi-In-Sn ternary system was re-examined in the study of Yoon et al [23] and the calculated phase diagram has both similarities and dissimilarities to the previously determined one. While the phase-transition temperatures are generally in agreement, the new phase diagram represents a different nature of the quasi-binaries, the number and type of the invariant reactions, and the reaction paths [23].…”
Section: Hcp_a3mentioning
confidence: 98%
See 3 more Smart Citations